An investigation of the dynamics of intramammary infections acquired during the dry period on European dairy farms - Bradley, Andrew J.; De Vliegher, S.; Green, Martin J.; Larrosa, P.; Payne, B.; van de Leemput, E. Schmitt; Samson, O.; Valckenier, D.; Van Werven, T.; Waldeck, H.W.F.; White, V.; Goby, L. (American Dairy Science Association, 2015)
The dry period is acknowledged as playing a key role in mastitis epidemiology and yet surprisingly few studies have explored dry period infection dynamics in detail. The aim of this study was to investigate the dynamics of intramammary infection across a cohort of dairy herds in Europe. Five hundred and twenty-two cows were recruited from 12 farms in 6 European countries. All cows received antibiotic dry cow therapy but teat sealants were not used. All quarters of all cows were sampled for bacteriology at drying off and in the week immediately postcalving. Two ipsilateral quarters were also sampled for bacteriology in each cow 2 and 6 wk after drying off. Cows were body condition scored and teats assessed for cleanliness at all sampling time points and for the presence of a keratin plug during the dry period. Other cow-level parameters such as historic somatic cell counts and milk yields before drying off were collated from farm records. Univariable and multivariable analyses were undertaken to investigate the etiology, prevalence, and dynamics of infection during the dry period and associated influential factors. In summary, environmental mastitis pathogens predominated. Although gram-positive major pathogens were typically well controlled and did not increase in prevalence across the dry period, gram-negative pathogens generally increased in prevalence. There was an increase in the number of quarters that yielded no growth across the dry period, although this was driven by minor rather than major mastitis pathogen control. Other than the presence of a gram-positive or gram-negative pathogen 6 wk after drying off, the measured parameters were not influential when considering their effect on the presence of pathogens postcalving. Analysis also suggested that the early and mid dry period may be more important with respect to the timing of acquisition of infection than previously thought. We observed substantial variation in the etiology and prevalence of different pathogens on different farms with, in all cases, at least one of the 12 herds experiencing the opposite of the others with respect to increases and decreases in pathogen prevalence. Overall, this study confirms the importance of the dry period in mastitis epidemiology but highlights the importance of assessing and understanding infection dynamics on individual units. The lack of influence of the cow and quarter factors measured in this study suggests that herd and management factors may be more influential.